Patents lite - Aussies pioneer a cheap and easy way to protect inventions. - Frank, S.J (IEEE spectrum)
This article discusses a cheap way to protect inventions known as the petty patent. It provides some patent-like protection, but the scope and duration of that protection is less than that for inventions that qualify for a standard patent. Although they are cheap and easy, it has its flaws depending on different countries. In a move to offer inventors more support, Australia revamped the petty patent. An Australian "innovation patent" as it is called, lasts for eight years and is not as restricted in terms of subject matter; anything that may be covered by a standard patent is likewise fair game under the innovation system. Innovation patents answer the need for quick protection in rapidly evolving industries.